Pathophysiology of NSAID-Associated Intestinal Lesions in the Rat: Luminal Bacteria and Mucosal Inflammation as Targets for Prevention - Colucci, Rocchina; Pellegrini, Carolina; Fornai, Matteo; Tirotta, Erika; Antonioli, Luca; Renzulli, Cecilia; Ghelardi, Emilia; Piccoli, Elena; Gentile, Daniela; Benvenuti, Laura; Natale, Gianfranco; Fulceri, Federica; et al. (Frontiers in Pharmacology, 2018)
Non-steroidal anti-inflammatory drugs (NSAIDs) exert detrimental effects on the intestine, mainly through an involvement of enteric bacteria This study examined the pathophysiology of NSAID-associated intestinal lesions in a rat model of diclofenac-enteropathy and evaluated the effect of rifaximin on small bowel damage. Enteropathy was induced in 40-week-old male rats by intragastric diclofenac (4 mg/kg BID, 14 days). Rifaximin (delayed release formulation) was administered (50 mg/kg BID) 1 hour before the NSAID. At the end of treatments, parameters dealing with ileal damage, inflammation, barrier integrity, microbiota composition and TLR-NFkB-inflammasome pathway were evaluated. In addition, the modulating effect of rifaximin on NLRP3 inflammasome was tested in an in vitro cell system. Diclofenac induced intestinal damage and inflammation, triggering an increase in tissue concentrations of tumor necrosis factor and interleukin-1, higher expression of TLR-2 and TLR-4, MyD88, NFB and activation of caspase-1. In addition, the NSAID decreased ileal occludin expression and provoked a shift of bacterial phyla towards an increase in Proteobacteria and Bacteroidetes abundance. All these changes were counterbalanced by rifaximin co-administration. The drug was also capable of increasing the proportion of Lactobacilli, a genus depleted by the NSAID. In LPS-primed THP-1 cells stimulated by nigericin (a model to study the NLRP3 inflammasome), rifaximin reduced IL-1 production in a dose-dependent fashion, this effect being associated with inhibition of the up-stream caspase-1 activation. In conclusion, diclofenac induced ileal mucosal lesions, driving inflammatory pathways and microbiota changes. Rifaximin prevents diclofenac-induced enteropathy through both antibacterial and anti-inflammatory activities.